2019
DOI: 10.4018/ijea.2019070101
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Self-Efficacy and Perceived Enjoyment in Predicting Computer Engineering Students' Continuous Use Intention of Scratch

Abstract: Scratch has been implemented as a preliminary programming environment to improve students' programming experience, motivation, and success in the Computer Science (CS) or Engineering departments. Acceptance and use of this visual programming environment by CS or Engineering students is a significant research area. Accordingly, this study investigated acceptance and use of Scratch programming environment by developing a theoretical model based on the Technology Acceptance Model (TAM). Structural equation modell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Items from sections 3 to 5 were answered by using a five-point Likert scale where 1 indicated strongly disagree and 5 represented strongly agree. To improve reliability and validity of the research instrument, questions from prior studies such as [59], [60] were adapted. In addition, reliability was ensured by pretesting the questionnaire to 15 academic staff members.…”
Section: Data Collection Instrumentmentioning
confidence: 99%
“…Items from sections 3 to 5 were answered by using a five-point Likert scale where 1 indicated strongly disagree and 5 represented strongly agree. To improve reliability and validity of the research instrument, questions from prior studies such as [59], [60] were adapted. In addition, reliability was ensured by pretesting the questionnaire to 15 academic staff members.…”
Section: Data Collection Instrumentmentioning
confidence: 99%
“…In this regard, Tsai et al (2014) showed that system self-efficacy can affect the PU and PEOU of telehealth systems. Similarly, Arpaci et al (2019) found that self efficacy has direct effect on the PEOU. Faqih (2013) examined consumer intention in Jordan and confirmed that the influence of Internet self-efficacy on PEOU was positive and that strong Internet self-efficacy affects PU positively with 99% confidence.…”
Section: Discussionmentioning
confidence: 89%
“…In other words, it is expected that raising self-efficacy by differentiating the difficulty between Beginners and Challengers will increase effort expectancy, and that hedonic motivation is related to perceived enjoyment [49]. Arpaci and Durdu (2019) and Arpaci (2021) applied the Scratch language, which was taught to computer science students, to TAM, and found that perceived enjoyment had a statistical impact on attitude, and the parameter does have an impact on continuous use intention [50,51]. In particular, perceived enjoyment has the greatest impact on attitude, which makes it deeply related to existing research [19].…”
Section: Conclusion and Discussionmentioning
confidence: 99%